Transformational-Generative Theory Perspective in Teaching The Four Language Skills of Arabic - Muhammad Jundi; Nabila Nabila (INAIFAS PRESS, 2023)
Language, as a communication tool, has drawn the attention of linguists to research and discover new theories about language. The Transformative-Generative Theory by Noam Chomsky is believed to have revolutionized the development of linguistics. This theory holds that human language ability is not a natural product, but an innate potential in humans since birth. This article examines how Arabic language learning can be viewed through the lens of the Transformative-Generative Theory. The research method used in this study is a qualitative approach with descriptive methods. Regarding language learning from the perspective of the transformative-generative theory, the four language skills are emphasized as follows: 1) listening comprehension, which requires language acquisition-based activities; 2) speaking, which relates to language creativity; 3) reading, which is related to competence and performance; and 4) writing, which is related to surface and deep structure. These concepts can be applied to writing instruction in analyzing and producing texts.